Virtual Surgical Planning for Oncologic Mandibular and Maxillary Reconstruction. Issue 9 (17th September 2021) - Myers, Paige L.; Nelson, Jonas A.; Rosen, Evan B.; Allen, Robert J.; Disa, Joseph J.; Matros, Evan
Abstract : Summary: Virtual surgical planning (VSP) with computer-aided design and computer-aided modeling (CAD/CAM) enables the opportunity to provide personalized medicine in complex head and neck reconstruction. This innovative technology allows ablative and reconstructive surgeons to virtually create and manipulate three-dimensional anatomic models to plan both the resection and reconstruction of complicated maxillofacial defects. Studies demonstrate improvements in preoperative planning, operative efficiency and accuracy, and postoperative outcomes. VSP facilitates immediate dental implantation in selected patients, which can improve the likelihood of achieving dental restoration. This article outlines strategies for technique optimization as well as the applications, advantages and disadvantages of VSP in complex oncologic head and neck reconstruction.